A method for preparing polyacrylamide conductive hydrogel using discarded lithium battery negative electrode

By screening, microwave processing and ultrasonic peeling of the negative electrode materials of waste lithium battery, polyacrylamide conductive hydrogel was prepared, which solved the problem of recycling and utilization of negative electrode materials of lithium battery in the prior art, and realized the preparation of high-value-added products and environmentally friendly treatment process.

CN115353643BActive Publication Date: 2025-03-14BEIJING ZHONGHUAN GUANGGUANG ENERGY TECHNOLOGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211170448.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-09-26
Publication Date
2025-03-14
Estimated Expiration
2042-09-26

AI Technical Summary

Technical Problem

The prior art is difficult to effectively recycle and utilize lithium battery negative electrode materials, especially graphite and other components, and the commonly used pickling method will produce new contaminants.

Method used

By screening and microwaveing ​​the negative electrode material of the waste lithium battery, combined with ultrasonic and magnetic stirring water-soluble separation process, graphene sheets are further obtained through ultrasonic peeling, and polyacrylamide conductive hydrogels are prepared using these components.

Benefits of technology

The complete recycling of the negative electrode material of lithium battery is achieved, and the prepared polyacrylamide hydrogel has good conductivity and mechanical properties, and does not produce new pollutants and is environmentally friendly.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of lithium battery treatment and hydrogel preparation, and provides a method for preparing polyacrylamide conductive hydrogel with discarded lithium battery negative electrode. The method selects discarded lithium battery graphite negative electrode material with styrene-butadiene latex as a binder, sodium carboxymethyl cellulose as a thickener, and conductive carbon black as a conductive agent, firstly performs microwave treatment on the negative electrode powder, then performs water-soluble separation, and performs ultrasonic stripping treatment on the undissolved solid components, and adds various recycled components when preparing polyacrylamide hydrogel by free radical polymerization to prepare conductive hydrogel. On the one hand, the present invention can realize the complete recycling of lithium battery negative electrode materials, and does not generate new pollutants, and has good environmental protection. On the other hand, the polyacrylamide hydrogel prepared by the present invention has good conductive properties and mechanical properties, has practical application value, and is economical.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium battery treatment and hydrogel preparation, and provides a method for preparing polyacrylamide conductive hydrogel by using the negative electrode of discarded lithium battery. Background Art

[0002] In recent years, lithium batteries have been widely used in transportation, power storage, mobile communications and other fields. As a result, the number of discarded lithium batteries has also increased. If not handled properly, they will harm the human body and the environment and cause waste of resources. At present, lithium battery recycling is mainly for positive electrode materials, and the recycling of negative electrode materials is less.

[0003] Most lithium batteries use graphite as the negative electrode material and contain additives. Currently, the vast majority of lithium battery negative electrodes use styrene-butadiene latex as a binder, sodium carboxymethyl cellulose as a thickener, and conductive carbon black as a conductive agent. At the same time, lithium batteries undergo a large number of cycles during use, and metal impurities will be deposited on the negative electrode graphite. Currently, negative electrode recycling mainly removes binders, thickeners, conductive agents, deposited metals, etc. to obtain high-purity graphite.

[0004] In the prior art, hydrochloric acid, nitric acid or sulfuric acid is often used to pickle the negative electrode, which can remove styrene butadiene, sodium carboxymethyl cellulose and deposited metals, but the waste liquid from pickling is not easy to dispose of and produces new pollutants; high-temperature pyrolysis is also used to remove additives, but this method cannot remove deposited metals and is prone to graphite oxidation. It can be seen that the prior art mainly recycles the graphite in the negative electrode, and other components are still discarded. Summary of the invention

[0005] The present invention provides a method for preparing polyacrylamide conductive hydrogel using waste lithium battery negative electrodes, aiming to fully utilize various components in the waste lithium battery negative electrodes and prepare high value-added products without generating new pollutants.

[0006] To achieve the above purpose, the specific technical solution of the present invention is as follows:

[0007] A method for preparing polyacrylamide conductive hydrogel using a discarded lithium battery negative electrode, the method comprising the following steps:

[0008] S1. Screening the negative electrode materials of waste lithium batteries, selecting the graphite negative electrode with styrene-butadiene latex as a binder, sodium carboxymethyl cellulose as a thickener, and conductive carbon black as a conductive agent, and grinding them into powder;

[0009] S2. The powder is subjected to microwave treatment, then added to deionized water, first subjected to ultrasonic treatment, then subjected to magnetic stirring, and filtered to obtain filtrate 1 and residue 1;

[0010] S3. The residue 1 was dispersed in N-methyl-2-pyrrolidone and subjected to ultrasonic treatment, filtered, and the obtained residue 2 and sodium dodecyl sulfate were added to deionized water and dispersed uniformly to obtain a dispersion;

[0011] S4. Add the dispersion to the filtrate 1, mix evenly, then add acrylamide, acrylic acid, persulfate, N,N'-methylenebisacrylamide, disperse evenly, and heat in a water bath to react to obtain polyacrylamide conductive hydrogel.

[0012] S1 is the screening of negative electrode materials. Since in the scheme of the present invention, each component in the negative electrode is a recycled material, in order to ensure the performance of the polyacrylamide conductive hydrogel product, attention should be paid to the screening process of the negative electrode materials.

[0013] S2 is the water-soluble separation process of the negative electrode material. The soluble substances are fully dissolved in deionized water by ultrasonic and magnetic stirring. The obtained filtrate 1 contains styrene-butadiene latex and sodium carboxymethyl cellulose, and the filter residue 1 is a mixture of expanded graphite, conductive carbon black, and deposited metal. Before the water-soluble separation, the present invention performs microwave treatment on the negative electrode powder to make the graphite initially peeled off and expanded, which is beneficial to the full dissolution of the soluble substances on the one hand, and is beneficial to the ultrasonic peeling of the subsequent S3 step on the other hand.

[0014] Preferably, in S2, the microwave frequency of the microwave treatment is 400-600 MHz, and the treatment time is 10-20 s.

[0015] Preferably, in S2, the ultrasonic frequency of the ultrasonic treatment is 20-30 kHz, and the treatment time is 10-15 min.

[0016] Preferably, in S2, the speed of magnetic stirring is 60-120 rpm, and the time is 40-60 min.

[0017] Further preferably, in S2, the mass ratio of powder to deionized water is 10-20:100.

[0018] S3 is ultrasonic stripping of the filter residue 1. In this process, the expanded graphite is stripped into graphene sheets through the intercalation effect of N-methyl-2-pyrrolidone and the ultrasonic-assisted destruction of the van der Waals force between graphite layers. At the same time, the conductive carbon black and the deposited metal are also separated from the graphite. The ultrasonic stripping method used in the present invention does not require the addition of a strong oxidant, and can obtain graphene sheets with low oxidation degree and good conductivity.

[0019] Preferably, in S3, the ultrasonic treatment has an ultrasonic frequency of 40-60 kHz and a duration of 10-15 h.

[0020] Further preferably, in S3, the mass ratio of the filter residue 1 to N-methyl-2-pyrrolidone is 0.01-0.02:100.

[0021] After the ultrasonic stripping is completed, a filter residue 2 containing graphene sheets, conductive carbon black, and deposited metal is obtained, and the filter residue 2 and sodium dodecyl sulfate are further dispersed in deionized water to prepare a dispersion.

[0022] Preferably, in S3, the mass ratio of the filter residue 2, sodium dodecyl sulfate and deionized water is 5-10:0.05-0.1:100.

[0023] S4 is a process for preparing conductive hydrogel by free radical polymerization. Among the raw materials of S4, acrylamide and acrylic acid are polymerization monomers; persulfate is an initiator; N,N'-methylenebisacrylamide is a crosslinker; graphene sheets, conductive carbon black and metals in the dispersion are used as conductive additives; styrene butadiene latex in filtrate 1 can participate in polymerization; sodium carboxymethyl cellulose is a common additive for preparing polyacrylamide hydrogel and has multiple functions.

[0024] Preferably, in S4, the persulfate is one of potassium persulfate, ammonium persulfate and sodium persulfate.

[0025] Preferably, in S4, the mass ratio of the dispersion, the filtrate 1, acrylamide, acrylic acid, persulfate, and N,N'-methylenebisacrylamide is 90-110:40-60:10:2-3:0.15-0.2:0.08-0.1.

[0026] More preferably, in S4, the reaction temperature is 50-60°C and the reaction time is 2.5-3.5h.

[0027] In the method of the present invention, the filtrate and filter residue produced by the water-soluble separation of the lithium battery negative electrode powder are used as raw materials for preparing polyacrylamide hydrogel, and the negative electrode material can be completely recycled. Moreover, after the filter residue 1 is ultrasonically stripped, N-methyl-2-pyrrolidone can be recovered and reused, so that no new pollutants are generated during the treatment process.

[0028] As is known, sodium carboxymethyl cellulose is a common additive for preparing polyacrylamide hydrogel, which can give the hydrogel interfacial adhesion and pH responsiveness. On this basis, the present invention peels graphite into graphene with stronger conductivity, and together with conductive carbon black and metal as conductive additives, it is loaded in the network structure of the hydrogel, which can give the hydrogel good conductivity, and these additives can also significantly improve the mechanical strength of the hydrogel. Further, the double bonds in styrene-butadiene latex can also participate in the polymerization reaction, thereby introducing the rigid group phenyl into the gel structure, which is conducive to further improving the mechanical strength of the hydrogel.

[0029] It can be seen that compared with the prior art, the technical solution of the present invention has the following beneficial effects: first, the present invention can realize the complete recycling of negative electrode materials of lithium batteries, and does not generate new pollutants, and has good environmental protection; second, the polyacrylamide hydrogel prepared by the present invention has good electrical conductivity and mechanical properties, has practical application value, and is economical. DETAILED DESCRIPTION

[0030] The present invention is further described in detail below through specific embodiments. Without departing from the method concept of the present invention, various substitutions or changes made according to the known technical knowledge and conventional means in the field should be included in the protection scope of the present invention.

[0031] First, the negative electrode materials of discarded lithium batteries are screened, and a graphite negative electrode with styrene-butadiene latex as a binder, sodium carboxymethyl cellulose as a thickener, and conductive carbon black as a conductive agent is selected, ground into powder, and mixed evenly; the powder is used to carry out subsequent preparation processes according to the processes of Examples 1-6.

[0032] Example 1

[0033] S2. The powder was treated with microwaves at a frequency of 400 MHz for 20 seconds, then added to deionized water, first treated with ultrasound at a frequency of 20 kHz for 15 minutes, then magnetically stirred at 120 rpm for 40 minutes, filtered to obtain filtrate 1 and residue 1; the mass ratio of powder to deionized water was 10:100;

[0034] S3. Disperse the filter residue 1 in N-methyl-2-pyrrolidone, the mass ratio of the filter residue 1 to N-methyl-2-pyrrolidone is 0.01:100, perform ultrasonic treatment at 60kHz for 10h, filter, add the obtained filter residue 2 and sodium dodecyl sulfate into deionized water, disperse evenly, and obtain a dispersion; the mass ratio of the filter residue 2, sodium dodecyl sulfate, and deionized water is 5:0.05:100;

[0035] S4. Add the dispersion to the filtrate 1, mix evenly, then add acrylamide, acrylic acid, ammonium persulfate, and N,N'-methylenebisacrylamide, disperse evenly, heat to 50°C and react for 3.5 hours to obtain polyacrylamide conductive hydrogel; the mass ratio of the dispersion, filtrate 1, acrylamide, acrylic acid, ammonium persulfate, and N,N'-methylenebisacrylamide is 90:40:10:2.5:0.15:0.08.

[0036] Example 2

[0037] S2. The powder was treated with microwaves at a frequency of 600 MHz for 10 seconds, then added into deionized water, firstly treated with ultrasound at a frequency of 30 kHz for 10 minutes, then magnetically stirred at 90 rpm for 50 minutes, filtered to obtain filtrate 1 and residue 1; the mass ratio of powder to deionized water was 10:100;

[0038] S3. Disperse the filter residue 1 in N-methyl-2-pyrrolidone, the mass ratio of the filter residue 1 to N-methyl-2-pyrrolidone is 0.015:100, perform ultrasonic treatment at 50kHz for 12h, filter, add the obtained filter residue 2 and sodium dodecyl sulfate into deionized water, disperse evenly, and obtain a dispersion; the mass ratio of the filter residue 2, sodium dodecyl sulfate, and deionized water is 5:0.05:100;

[0039] S4. Add the dispersion to the filtrate 1, mix evenly, then add acrylamide, acrylic acid, ammonium persulfate, and N,N'-methylenebisacrylamide, disperse evenly, heat to 55°C to react for 3 hours, and obtain polyacrylamide conductive hydrogel; the mass ratio of the dispersion, filtrate 1, acrylamide, acrylic acid, ammonium persulfate, and N,N'-methylenebisacrylamide is 90:40:10:2.5:0.15:0.08.

[0040] Example 3

[0041] S2. The powder was treated with microwaves at a frequency of 550 MHz for 12 seconds, then added to deionized water, first treated with ultrasound at a frequency of 20 kHz for 13 minutes, then magnetically stirred at 80 rpm for 55 minutes, filtered, and filtrate 1 and residue 1 were obtained; the mass ratio of powder to deionized water was 10:100;

[0042] S3. Disperse the filter residue 1 in N-methyl-2-pyrrolidone, the mass ratio of the filter residue 1 to N-methyl-2-pyrrolidone is 0.01:100, perform ultrasonic treatment at 60kHz for 12h, filter, add the obtained filter residue 2 and sodium dodecyl sulfate into deionized water, disperse evenly, and obtain a dispersion; the mass ratio of the filter residue 2, sodium dodecyl sulfate, and deionized water is 5:0.05:100;

[0043] S4. Add the dispersion to the filtrate 1, mix evenly, then add acrylamide, acrylic acid, ammonium persulfate, and N,N'-methylenebisacrylamide, disperse evenly, heat to 60°C and react for 2.5 hours to obtain polyacrylamide conductive hydrogel; the mass ratio of the dispersion, filtrate 1, acrylamide, acrylic acid, ammonium persulfate, and N,N'-methylenebisacrylamide is 90:40:10:2.5:0.15:0.08.

[0044] Example 4

[0045] S2. The powder was treated with microwaves at a frequency of 500 MHz for 15 seconds, then added to deionized water, first treated with ultrasound at a frequency of 25 kHz for 10 minutes, then magnetically stirred at 60 rpm for 60 minutes, filtered to obtain filtrate 1 and residue 1; the mass ratio of powder to deionized water was 20:100;

[0046] S3. Disperse the filter residue 1 in N-methyl-2-pyrrolidone, the mass ratio of the filter residue 1 to N-methyl-2-pyrrolidone is 0.02:100, perform ultrasonic treatment at 40kHz for 15h, filter, add the obtained filter residue 2 and sodium dodecyl sulfate into deionized water, disperse evenly, and obtain a dispersion; the mass ratio of the filter residue 2, sodium dodecyl sulfate, and deionized water is 10:0.1:100;

[0047] S4. Add the dispersion to the filtrate 1, mix evenly, then add acrylamide, acrylic acid, ammonium persulfate, and N,N'-methylenebisacrylamide, disperse evenly, heat to 50°C and react for 3.5 hours to obtain polyacrylamide conductive hydrogel; the mass ratio of the dispersion, filtrate 1, acrylamide, acrylic acid, ammonium persulfate, and N,N'-methylenebisacrylamide is 110:60:10:2.5:0.15:0.08.

[0048] Example 5

[0049] S2. The powder was treated with microwaves at a frequency of 450 MHz for 15 seconds, then added to deionized water, first treated with ultrasound at a frequency of 25 kHz for 15 minutes, then magnetically stirred at 100 rpm for 50 minutes, filtered, and filtrate 1 and residue 1 were obtained; the mass ratio of powder to deionized water was 20:100;

[0050] S3. Disperse the filter residue 1 in N-methyl-2-pyrrolidone, the mass ratio of the filter residue 1 to N-methyl-2-pyrrolidone is 0.02:100, perform ultrasonic treatment at 60kHz for 15h, filter, add the obtained filter residue 2 and sodium dodecyl sulfate into deionized water, disperse evenly, and obtain a dispersion; the mass ratio of the filter residue 2, sodium dodecyl sulfate, and deionized water is 10:0.1:100;

[0051] S4. Add the dispersion to the filtrate 1, mix evenly, then add acrylamide, acrylic acid, ammonium persulfate, and N,N'-methylenebisacrylamide, disperse evenly, heat to 55°C to react for 3 hours, and obtain polyacrylamide conductive hydrogel; the mass ratio of the dispersion, filtrate 1, acrylamide, acrylic acid, ammonium persulfate, and N,N'-methylenebisacrylamide is 110:60:10:2.5:0.15:0.08.

[0052] Example 6

[0053] S2. The powder was treated with microwaves at a frequency of 600 MHz for 15 seconds, then added into deionized water, firstly treated with ultrasound at a frequency of 28 kHz for 12 minutes, then magnetically stirred at 90 rpm for 50 minutes, filtered to obtain filtrate 1 and residue 1; the mass ratio of powder to deionized water was 20:100;

[0054] S3. Disperse the filter residue 1 in N-methyl-2-pyrrolidone, the mass ratio of the filter residue 1 to N-methyl-2-pyrrolidone is 0.015:100, perform ultrasonic treatment at 40kHz for 15h, filter, add the obtained filter residue 2 and sodium dodecyl sulfate into deionized water, disperse evenly, and obtain a dispersion; the mass ratio of the filter residue 2, sodium dodecyl sulfate, and deionized water is 10:0.1:100;

[0055] S4. Add the dispersion to the filtrate 1, mix evenly, then add acrylamide, acrylic acid, ammonium persulfate, and N,N'-methylenebisacrylamide, disperse evenly, heat to 60°C and react for 2.5 hours to obtain polyacrylamide conductive hydrogel; the mass ratio of the dispersion, filtrate 1, acrylamide, acrylic acid, ammonium persulfate, and N,N'-methylenebisacrylamide is 110:60:10:2.5:0.15:0.08.

[0056] Performance Test:

[0057] (1) The electrical conductivity of the hydrogels of Examples 1-6 was tested by a two-point probe, and the results were 9.41 S / m, 9.57 S / m, 9.46 S / m, 11.13 S / m, 11.28 S / m, and 11.18 S / m, respectively.

[0058] (2) The hydrogels of Examples 1-6 were respectively made into dumbbell-shaped specimens (30 mm in length, 4 mm in width, and 1 mm in thickness). The tensile strengths were measured using a universal testing machine at a tensile speed of 80 mm / min. The results were as follows:

[0059] (3) The hydrogels of Examples 1-6 were respectively made into cylindrical samples (diameter 15 mm, height 10 mm). The compressive strengths were measured using a universal testing machine at a compression speed of 30 mm / min. The results were as follows: 0.72 MPa, 0.77 MPa, 0.74 MPa, 0.91 MPa, 0.98 MPa, and 0.94 MPa, respectively.

[0060] It can be seen that the polyacrylamide hydrogel prepared by adding the recycled components of the discarded lithium battery negative electrode material has good electrical conductivity and mechanical properties and has practical application value.

Claims

1. A method for preparing polyacrylamide conductive hydrogel using waste lithium battery negative electrode, characterized in that: The method comprises the following steps: S1. Screening the negative electrode materials of waste lithium batteries, selecting the graphite negative electrode with styrene-butadiene latex as a binder, sodium carboxymethyl cellulose as a thickener, and conductive carbon black as a conductive agent, and grinding them into powder; S2. The powder is subjected to microwave treatment, then added to deionized water, first subjected to ultrasonic treatment, then subjected to magnetic stirring, and filtered to obtain filtrate 1 and residue 1; S3. The residue 1 was dispersed in N-methyl-2-pyrrolidone and subjected to ultrasonic treatment, filtered, and the obtained residue 2 and sodium dodecyl sulfate were added to deionized water and dispersed uniformly to obtain a dispersion; S4. Add the dispersion to the filtrate 1, mix evenly, then add acrylamide, acrylic acid, persulfate, N,N'-methylenebisacrylamide, disperse evenly, and heat in a water bath to react to obtain polyacrylamide conductive hydrogel.

2. The method for preparing polyacrylamide conductive hydrogel using waste lithium battery negative electrode according to claim 1, characterized in that: In S2, the microwave frequency of the microwave treatment is 400-600 MHz, and the treatment time is 10-20 s; the ultrasonic frequency of the ultrasonic treatment is 20-30 kHz, and the treatment time is 10-15 min; the speed of the magnetic stirring is 60-120 rpm, and the time is 40-60 min.

3. The method for preparing polyacrylamide conductive hydrogel using discarded lithium battery negative electrode according to claim 1, characterized in that: In S2, the mass ratio of powder to deionized water is 10-20:

100.

4. The method for preparing polyacrylamide conductive hydrogel using waste lithium battery negative electrode according to claim 1, characterized in that: In S3, the ultrasonic treatment is performed at an ultrasonic frequency of 40-60 kHz and for a time of 10-15 h.

5. The method for preparing polyacrylamide conductive hydrogel using waste lithium battery negative electrode according to claim 1, characterized in that: In S3, the mass ratio of the filter residue 1 and N-methyl-2-pyrrolidone is 0.01-0.02:

100.

6. The method for preparing polyacrylamide conductive hydrogel using waste lithium battery negative electrode according to claim 1, characterized in that: In S3, the mass ratio of filter residue 2, sodium dodecyl sulfate and deionized water is 5-10:0.05-0.1:

100.

7. The method for preparing polyacrylamide conductive hydrogel using waste lithium battery negative electrode according to claim 1, characterized in that: In S4, the persulfate is one of potassium persulfate, ammonium persulfate and sodium persulfate.

8. The method for preparing polyacrylamide conductive hydrogel using waste lithium battery negative electrode according to claim 1, characterized in that: In S4, the mass ratio of the dispersion, the filtrate 1, acrylamide, acrylic acid, persulfate, and N,N'-methylenebisacrylamide is 90-110:40-60: 10:2-3:0.15-0.2:0.08-0.1。 9. The method for preparing polyacrylamide conductive hydrogel using waste lithium battery negative electrode according to claim 1, characterized in that: In S4, the reaction temperature is 50-60°C and the reaction time is 2.5-3.5h.

Citation Information

Patent Citations

  • Treatment method for recycling negative electrode material of lithium-ion battery

    CN106129521A

  • Lithium battery material recycling method

    CN112397801A

  • Improved lithium batteries recycling process

    WO2023240334A1